Microneedling with topical administration of bleomycin as a treatment method for plantar warts - Michał Smoczok; Szymon Leonik; Beata Bergler-Czop; Katarzyna Nowak (Przegląd Dermatologiczny, 2022)
Plantar warts are a viral disease caused by a broad spectrum of HPV viruses (in particular HPV 1, 2, 27 and 57), with a frequency of 7–14% in the general population. Bleomycin, a cytostatic used in the treatment of plantar warts, shows variable efficacy in the conducted studies (16–97% cure rate), depending on the concentration used and the method of administration of the drug. One of the methods of increasing the efficacy of bleomycin is the use of microneedling, a procedure that creates a series of channels to improve penetration of the substance. It has shown an improvement in the response time to bleomycin treatment of plantar warts, as well as a reduction in the number of treatment sessions required. The rate of relapse using this method is similar to that of other injection-based methods.